What knowledge is needed? Teaching undergraduate medical students to “go upstream” and advocate on social determinants of health - Hayman, Kate; Wen, Mei; Khan, Farooq; Mann, Tracey; Pinto, Andrew D.; Ng, Stella L. (Canadian Medical Education Journal, 2020)
Background: We rarely teach medical students the skills required to engage in policy change to address the structural factors that underpin the social determinants of health, which are driven by the unequal distribution of power and resources in society. Acquiring the knowledge and skills to influence policy can empower students to act on healthcare inequities rather than simply be aware of them. Methods: Using Metzl and Hansen’s structural competency framework, we designed and piloted an intervention for medical students. Participants attended a workshop, presented to a hypothetical political stakeholder, and wrote an opinion editorial piece. Students participated in a focus group that was audio-recorded and transcribed. We coded and analyzed presentations, editorials, and transcripts to develop a thematic analysis. Results: Nine students participated in the workshop. They chose structural interventions and presented potential solutions to structural barriers in written and oral outputs. Students identified a lack of knowledge about health and political systems as a potential barrier to future advocacy work. Conclusion: Medical trainees require training in specific advocacy skills such as oral and written communication, however this alone may be insufficient. As future advocates, trainees must also acquire a specific skill set and associated knowledge about health systems and policy to navigate the systems in which they will practice.